Complement Factor B Polymorphism and the Phenotype of Early Age-related Macular Degeneration. (March 2014) - Mantel, Irmela; Ambresin, Aude; Moetteli, Leila; Droz, Ivaine; Roduit, Raphaël; Munier, Francis L.; Schorderet, Daniel F.
Abstract Purpose: Age-related macular degeneration (AMD) has been associated with a number of polymorphisms in genes in the complement pathway. We examined the potential genotype–phenotype correlation of complement factor B (CFB) (R32Q) polymorphisms in Caucasian patients with AMD. Methods: Data from a Central European cohort of 349 patients with early AMD in at least one eye were analyzed for potential associations of the CFB (R32Q/rs641153) polymorphism with phenotypic features of early AMD. Early AMD was classified according to the International Classification and Grading System into predominant drusen size, largest drusen, drusen covered surface, central or ring-like location, peripheral drusen, and pigmentary changes. The potential association with single nucleotide polymorphisms on CFB (R32Q/rs641153) was evaluated for all patients, corrected for age, sex, and the polymorphisms of CFH (Y402H) and ARMS2 (A69S). Results: CFB (R32Q) polymorphisms showed a significant association with smaller drusen size (largest drusen ≤250 µm, p = 0.021, predominant drusen ≤125 µm, p = 0.016), with smaller surface covered by drusen (≤10%; p = 0.02), and with more frequent occurrence of peripheral drusen (p = 0.007). No association was found for pigmentary changes. Conclusions: The CFB (R32Q) polymorphism was associated with AMD characterized by small drusen only, and appeared to be protective of large drusen (OR 0.48/0.45) and of larger drusen covered area (OR 0.34). Furthermore, peripheral drusen were more frequently found (OR 2.27). This result supports the role of complement components and their polymorphisms in drusen formation and may enable a better understanding of AMD pathogenesis.